The Efficacy of Cephalosporin Antibiotics Against Urinary Tract Infection (UTI)-Causing Bacteria - Saleh, Ali Y.A. (Indonesian Journal on Health Science and Medicine, 2025)
Urinary tract infections (UTIs) represent one of the most common bacterial infections worldwide, with over 150 million cases annually, causing significant health and economic burdens. Cephalosporins, a class of β-lactam antibiotics, are widely prescribed for UTIs due to their broad-spectrum activity and low toxicity; however, increasing resistance limits their effectiveness. Despite their extensive use, little is known about the prevalence of resistance mechanisms such as biofilm formation and β-lactamase production in UTI pathogens against different generations of cephalosporins in Baghdad. This study aimed to evaluate the efficacy of 14 cephalosporin antibiotics against UTI-causing bacteria, with particular focus on resistance rates, biofilm formation, and β-lactamase enzyme production. From 140 bacterial isolates, Escherichia coli was the predominant pathogen (82.14%), with infections occurring more frequently in females (84.95%). Resistance to cephalosporins was high (68.5%), particularly against second-generation cefuroxime (97.8%), whereas cefepime, a fourth-generation antibiotic, showed the highest sensitivity (30%). Biofilm production was detected in 62.2% of isolates, while β-lactamase production was observed in 63.5%, both contributing to multidrug resistance. This research provides the first comprehensive evaluation of cephalosporin efficacy against UTI pathogens in Baghdad, combining antimicrobial susceptibility testing with virulence factor analysis. The findings highlight the urgent need for continuous surveillance of antibiotic resistance, rational prescription practices, and consideration of advanced-generation cephalosporins or alternative therapies to manage UTIs effectively. Highlights: Escherichia coli accounted for 82.14% of UTI cases, with infections significantly higher in females (84.95%) than males. Bacterial isolates showed a high resistance rate of 68.5% to cephalosporin antibiotics, with the highest resistance to cefuroxime (97.8%). Virulence factors were prominent, with 62.2% of isolates forming biofilms and 63.5% producing β-lactamase enzymes.